Haematological Studies of Nili-Ravi Buffaloes Injected with Recombinant Bovine Somatotropin - T. Khaliq and Z. U. Rahman* (Pakistan Veterinary Journal, 2010)
Sixteen lactating Nili-Ravi buffaloes were used to observe the effect of recombinant bovine somatotropin (rbST) on haematological profile. These buffaloes were divided into two groups, with eight buffaloes in each group. Buffaloes of group I were injected with sterilized normal saline to serve as control. Animals in group II were administered 500 mg of rbST subcutaneously, twice at an interval of 16 days. Blood with anticoagulant was collected to determine DLC, ESR and PCV. Overall mean ESR decreased significantly (5.74%) in rbST injected buffaloes as compared to control at the end of experimental period. Neutrophils percent decreased and lymphocytes percent increased significantly in rbST treated buffaloes compared to control. Packed cell volume, basophils, monocytes and eosinophils did not differ significantly between the two groups. In conclusion, high dose of rbST did not result in alteration of certain haematological parameters in buffaloes.